Site-specific relationships between algal biomass and floating photovoltaic solar energy in human-made bodies of water - Cagle, Alexander E.; Narwold, Benjamin P.; Armstrong, Alona; Sadro, Steven; Pasquale, Giulia; Di Blasi, Miriam Lucia Vincenza; Hernandez, Rebecca R. (Frontiers in Water, 2025)
Eutrophication and climate-driven warming are degrading aquatic ecosystems by promoting harmful algal and cyanobacterial growth, while global decarbonization efforts are intensifying land-use conflicts for renewable energy. Floating solar photovoltaic (FPV) systems—solar panels installed on human-made waterbodies—offer a potential solution, yet their effects on algae and water quality remain poorly understood. We assessed algal biomass and water quality beneath FPVs and in open water at four FPV-hosting ponds across the United States, spanning a range of FPV coverage levels, trophic states, climates, and bathymetry. Sampling occurred twice daily across all seasons from 2021 to 2022. Results showed minimal overall differences in phycocyanin, chlorophyll-a, dissolved oxygen, pH, conductivity, and temperature between FPV-covered and open-water areas, though some site-specific trends emerged. At one mesotrophic site (4.8% coverage), chlorophyll-a and phycocyanin were significantly lower beneath FPVs in multiple seasons, with up to 80% reductions in chlorophyll-a observed in spring. In contrast, at a eutrophic site (22% coverage), chlorophyll-a was occasionally higher beneath FPVs, while two mesotrophic sites with high coverage (60–71%) showed no consistent differences. Dissolved oxygen and temperature exhibited limited site-specific variations but no consistent trends across FPVs. Overall, within-pond differences in algal biomass and water quality between FPV-covered and open-water areas were largely minimal, underscoring the need for further research with more FPV sites, before–after control–impact designs, and high-frequency monitoring to better understand FPV–algae interactions and potential water quality benefits.